2021
DOI: 10.1080/0144929x.2021.1945685
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to social influence strategies and persuasive system design: exploring the relationship

Abstract: Cialdini's six principles of influence are commercially used but less common to encourage healthy behaviors. This study examines how these influence strategies relate to the persuasive systems design (PSD) model constructs implemented in commercial mobile fitness applications. Our research questions address whether susceptibility to influence strategies strengthen the relationships between persuasive constructs and, if so, which strategies and software features are promising to leverage the persuasive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
(86 reference statements)
1
1
0
Order By: Relevance
“…Providing discount, giving limited time, and uniqueness were the most observed micro-strategies in ads for persuading language learners. Our findings are in line with a number of studies that also found that ‘reciprocity’ is the most used and most effective persuasive technique (Goodman-Delahunty & Howes, 2014b ; Halttu & Kukkonen, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…Providing discount, giving limited time, and uniqueness were the most observed micro-strategies in ads for persuading language learners. Our findings are in line with a number of studies that also found that ‘reciprocity’ is the most used and most effective persuasive technique (Goodman-Delahunty & Howes, 2014b ; Halttu & Kukkonen, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…Nevertheless, this model does not explain in detail the implementation strategies. To overcome the limitation in FBM, Oinas-Kukkonen et al (2017, 2021b) adopted Fogg's FBM and formulated a Persuasive System Design (PSD) suggesting four main categories in the persuasion process -primary task support, dialogue support, system credibility, and social support. The model suggests seven design principles under each of the four categories, thus totaling 28 design principles.…”
Section: Outcomes/benefits Of Using Persuasive Techniquesmentioning
confidence: 99%